2022
DOI: 10.1126/sciadv.add3555
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable valorization of asphaltenes via flash joule heating

Abstract: The refining process of petroleum crude oil generates asphaltenes, which poses complicated problems during the production of cleaner fuels. Following refining, asphaltenes are typically combusted for reuse as fuel or discarded into tailing ponds and landfills, leading to economic and environmental disruption. Here, we show that low-value asphaltenes can be converted into a high-value carbon allotrope, asphaltene-derived flash graphene (AFG), via the flash joule heating (FJH) process. After successful conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The resulting "flash" graphene (FG) is turbostratic [14] and less defective than graphene made by the reduction of graphene oxide. [15] flash Joule heating (FJH) enables rapid, inexpensive graphene synthesis from any carbon-containing feedstock, including rubber tires, [16] metallurgical coke, [17,18] asphaltenes, [19] and carbon black. [20][21][22] In addition to CO 2 emission concerns, plastic pollution is also a significant environmental problem.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting "flash" graphene (FG) is turbostratic [14] and less defective than graphene made by the reduction of graphene oxide. [15] flash Joule heating (FJH) enables rapid, inexpensive graphene synthesis from any carbon-containing feedstock, including rubber tires, [16] metallurgical coke, [17,18] asphaltenes, [19] and carbon black. [20][21][22] In addition to CO 2 emission concerns, plastic pollution is also a significant environmental problem.…”
Section: Introductionmentioning
confidence: 99%
“…The asphaltene-derived flash graphene showed improved mechanical, thermal, and anticorrosion properties for the composites compared to the bare polymer. [17] Research on the structure of asphaltene has revealed that it primarily consists of polycyclic aromatic hydrocarbons with alkane branches, as well as other heteroatoms such as O and N. [8,18] In this study, we employed the supercritical method to assemble nano-scale asphaltene units into ethylated carbon clusters (ECC). This assembly was achieved through molecular electrostatic attraction and 𝜋-𝜋 * interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The asphaltene‐derived flash graphene showed improved mechanical, thermal, and anti‐corrosion properties for the composites compared to the bare polymer. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our research group demonstrated that flash Joule heating (FJH) could be used to synthesize flash graphene (FG) from a variety of different feedstocks, including waste plastic, coffee grounds, asphaltenes, soybean oil, and rubber tires . The resulting FG is turbostratic and more easily dispersed in composites than graphene produced from exfoliation of graphite .…”
Section: Introductionmentioning
confidence: 99%